Analysis of the emotional and physical state of patients with neuromuscular diseases before and after rehabilitation using a visual analogue scale - Ermatov Ulugbek (Genius Journals, 2023)
The timely appointment of rehabilitation measures for patients with neuromuscular diseases (NMS) is an important step in planning care for patients in this group, since it helps prevent the development of emergency conditions and complications, reduce the number and duration of hospitalizations, slow down the progression of the underlying disease, increase social activity, and in some cases - Maintain employment. When selecting rehabilitation measures, it is important to analyze the load tolerance, assessing the level of emotional comfort and physical condition.
Keywords: Muscular dystrophies; neuromuscular diseases; rehabilitation